Using XFEM to Predict the Damage with Temperature of the Steel Pipe Elbows under Bending and Pressure loading - Nourddine Hammadi; Moahmed Mokhtari; Habib Benzaama; Kouider Madani; Abdelkader Brakna; Elamine Abdelouahed (Fracture and Structural Integrity)
The pipes, during their service, are subjected to accumulated loads such as internal pressure and that of the soil. The latter considerably accelerate their damage. In this work, the bending moment stress of API 5L X70 category steel elbows under thermo-mechanical behavior and in the presence of pressure were studied. We used FEM (finite element method) through the numerical calculation code ABAQUS and the XFEM technique for structural damage while using solid elements as a structure. Our objective is to evaluate the response and resistance capacity of the steel elbow by its location in the tube–elbow-tube system under a mixed loading of pressure and moment for all scenarios. It is based on a single standardized dimensioning of the elbow (diameter and thickness). The effect of several parameters has been studied such as the type of loading and the pressure levels, which are clearly conditioned by the level of damage. Numerical damage results are presented by moment-rotation curves. They illustrate the variation in damage as a function of these effects which act simultaneously.